The use of geographical weighted regression (GWR) to determine location influence for the rental value of the shop house - Oliver Valentine Eboy, author; Ibrahim Sipan, author; Buang Alias, author; Dzurllkanian @ Zulkarnain Daud, 1963-, author; REER Inaugural Meeting & Seminar (2005: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2005)
PSZJBL